Brain activity study on olfactory stimulation via electroencephalography - Ho, Melvin Weiyuan (2013)
Electroencephalography (EEG) is the recording of electrical signals generated by the brain. EEG had been used for past diagnostic application in neurology. EEG proves to be a important instrument in research, especially when higher temporal resolution is needed. [3rd Award]